The Shinus molle essential oil against Aspergillus parasiticus and Cladosporium cladosporiodes - Quintana-Obregón, Eber; Vargas-Arispuro, Irasema; Martínez-Téllez, Miguel Ángel; Gaxiola-Camacho, Soila Maribel (Comunicata Scientiae, 2025)
Aspergillus parasiticus and Cladosporium cladosporioides are fungi that present significant health risks. This study explored the antifungal potential of Shinus molle essential oil, a plant with a rich cultural history of medicinal and environmental uses. The essential oil was extracted from the leaves of Shinus molle using hydrodistillation and characterized by gas chromatography. The mean inhibitory concentration (IC50) and minimum inhibitory concentration (MIC) were established based on the radial growth of A. parasiticus and C. cladosporioides. The IC50 of the essential oil was specifically evaluated to assess spore germination. The primary compounds identified in the essential oil of S. molle included α-pinene, α-phellandrene, and γ-elemene. The findings revealed that the essential oil inhibited over 50% of the radial growth of both fungi after 96 hours. However, no significant differences were observed in the IC50 values for spore germination at 24 hours compared to the controls. The MIC recorded was notably high for the fungi evaluated. This study suggests that while S. molle essential oil does not inhibit the germination of A. parasiticus and C. cladosporioides, it restricts their growth radial at elevated concentrations.